MOFs / modified carbon nanotube-based composite proton exchange membrane and preparation method thereof
The carbon nanotubes are coated through the surface deposition-crosslinking method and combined with citric acid and MOFs, the problem of insufficient mechanical properties and conductivity of chitosan proton exchange membrane is solved, and the high-performance composite proton exchange membrane preparation is achieved, which significantly improves the Mechanical and conductive properties of the membrane.
Patent Information
- Application Number
- CN202411301677.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
AI Technical Summary
The existing pure chitosan proton exchange membrane and its modified membrane have poor mechanical properties and conductivity, and the inhomogeneity caused by poor interfacial compatibility of organic-inorganic composite materials affects the comprehensive performance of the proton exchange membrane.
The surface deposition-crosslinking method is used to coat chitosan carbon nanotubes, and the citric acid molecule reacts with chitosan, and in situ reaction is carried out to prepare MOFs/modified carbon nanotubes to enhance interface interaction and Dispersibility, forming a composite proton exchange membrane.
It effectively improves the mechanical properties and proton conductivity of the composite proton exchange membrane, achieves good compatibility between CNT and chitosan substrate and uniform dispersion of MOFs, significantly improving the overall performance of the membrane.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of proton exchange membranes, and in particular to a composite proton exchange membrane based on MOFs / modified carbon nanotubes and a preparation method thereof. Background Art
[0002] Fuel cells, as a new type of energy conversion device, have many advantages such as high energy conversion rate, environmental friendliness, simple structure, and easy operation, and have attracted widespread attention from researchers. Proton exchange membrane fuel cells (PEMFCs), as a type of fuel cell, have the advantages of low operating temperature, fast startup speed at room temperature, simple structure, no electrolyte loss, high specific power and specific energy, easy operation, and long service life. They are ideal power sources for decentralized power stations, mobile power sources, electric vehicles, mobile communications, etc., and are also the best home power source. Among them, proton exchange membranes (PEMs) are the core components of proton exchange membrane fuel cells. They not only act as diaphragms to separate the positive and negative poles of the battery, but also play the role of transferring protons and blocking electrons in the battery. Their performance directly determines the performance of the fuel cell. Excellent PEMs materials need to have high proton conductivity (proton conductivity>0.01 S cm -1 ), good fuel barrier properties and excellent mechanical properties, while taking into account the actual needs of low cost and easy large-scale production.
[0003] Natural polymer materials have rapidly become the ideal choice for new proton exchange membrane materials due to their abundant sources, low prices, and environmental friendliness. Among them, chitosan (CS), as a biomass polysaccharide, has the advantages of low price, environmental friendliness, good hydrophilicity and film-forming properties, and low methanol permeability. Moreover, its main chain structure contains functional groups such as -OH and -NH2, which are easy to be chemically modified, making it an ideal polymer electrolyte membrane material.
[0004] However, the mechanical properties of pure CS membrane are poor, and -OH and -NH2 in its structure are very easy to form intramolecular and intermolecular hydrogen bonds, resulting in a high proportion of rigid crystalline regions in the membrane, making it difficult for ions to migrate in the membrane, resulting in unsatisfactory conductivity. Therefore, how to effectively implement modification treatment to improve chitosan conductivity while having good mechanical properties is the key to applying chitosan to proton exchange membrane materials. Organic-inorganic composite modification is a more commonly used polyelectrolyte modification strategy. By adding specific inorganic functional materials, the excellent properties of different functional materials can be effectively utilized to prepare composite proton exchange membrane materials with better performance. Carbon nanotubes (CNTs), as an excellent carbon nanomaterial, have a large aspect ratio, excellent mechanical properties and stability. They are an ideal material for preparing organic-inorganic composite membranes, especially for effectively improving the mechanical properties of composite materials. However, due to the difference in properties between organic and inorganic substances, a clear interface is often formed between the two, and the compatibility is poor, which easily leads to poor CNT dispersion, resulting in uneven proton exchange membranes and unsatisfactory comprehensive performance.
[0005] In recent years, MOFs, as a new type of proton conductive material, has attracted much attention in the field of preparation of high-efficiency proton exchange membranes. Combining conductive MOFs materials with CNTs may prepare an interactive composite material system. However, how to construct an effective interaction between MOFs and CNTs, while achieving a good interfacial interaction between CNTs and the organic polyelectrolyte matrix to show unique performance advantages, is a problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a composite proton exchange membrane based on MOFs / modified carbon nanotubes and a preparation method, and solve the technical problems in the prior art that pure chitosan proton exchange membrane or its modified membrane has poor mechanical properties and conductivity.
[0007] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes, comprising the following steps: adding carbon nanotubes to a first chitosan solution and dispersing them evenly, adjusting the pH value to alkaline, adding a cross-linking agent for cross-linking reaction, and obtaining CS@CNT; adding CS@CNT to a citric acid solution for reaction, and obtaining CCS@CNT; adding CCS@CNT to an organic solvent, and then adding MOFs raw materials, and obtaining MOFs / modified carbon nanotubes through an in-situ reaction; adding MOFs / modified carbon nanotubes to a second chitosan solution and dispersing them evenly, and obtaining a casting solution, and obtaining a composite proton exchange membrane based on MOFs / modified carbon nanotubes through film casting.
[0008] In a second aspect, the present invention provides a composite proton exchange membrane based on MOFs / modified carbon nanotubes prepared by the above preparation method.
[0009] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses chitosan to coat carbon nanotubes, which can not only effectively improve the interface interaction and compatibility between CNT and chitosan matrix, but also improve the dispersibility of CNT in chitosan matrix, and play the role of CNT in enhancing mechanical properties, thereby effectively improving mechanical properties; at the same time, the chitosan surface contains rich amino (-NH2) and hydroxyl (-OH) functional groups, which are connected to citric acid molecules through chemical reaction, and the strong metal ion chelating and coordination ability of citric acid molecules is utilized to realize the controllable preparation of conductive MOFs on the surface of CCS@CNT, and then a new proton exchange membrane is prepared by compounding with chitosan matrix, thereby effectively improving the conductive performance; the composite proton exchange membrane obtained by the present invention has excellent mechanical properties and proton conductivity. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0011] At present, the mechanical properties of pure CS membrane are poor, and the -OH and -NH2 in its structure are very easy to form intramolecular and intermolecular hydrogen bonds, so that there is a high proportion of rigid crystalline areas in the membrane, and ions are difficult to migrate in the membrane, resulting in unsatisfactory conductivity; and through organic-inorganic composite modification, such as composite carbon nanotubes (CNTs), due to the difference in properties between organic and inorganic substances, an obvious interface is often formed between the two, and the compatibility is poor, which easily leads to poor CNT dispersion, resulting in uneven proton exchange membranes and unsatisfactory comprehensive performance; in recent years, MOFs, as a new type of proton conductive material, has attracted much attention in the field of preparation of high-efficiency proton exchange membranes, and it is expected to combine conductive MOFs materials with CNTs, but how to construct an effective interaction between MOFs and CNTs, and at the same time achieve a good interface interaction between CNTs and organic polyelectrolyte matrix, that is, the specific combination mode of MOFs, CNTs and chitosan matrix and whether they can finally present performance advantages is a major difficulty. Based on this, the present invention is established.
[0012] In a first aspect, the present invention provides a method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes, comprising the following steps: (1) adding carbon nanotubes to a first chitosan solution to obtain a first dispersion; adjusting the pH value of the first dispersion to alkaline, and then adding a cross-linking agent to perform a cross-linking reaction to obtain chitosan-coated carbon nanotubes CS@CNT; (2) adding CS@CNT into citric acid solution to react and obtain chitosan-modified carbon nanotubes CCS@CNT; (3) adding CCS@CNT into an organic solvent to obtain a second dispersion; adding a raw material of MOFs into the second dispersion to obtain MOFs / modified carbon nanotubes through an in-situ reaction; (4) adding MOFs / modified carbon nanotubes to the second chitosan solution and dispersing them evenly to obtain a casting solution; and forming the casting solution into a film by casting to obtain a composite proton exchange membrane based on MOFs / modified carbon nanotubes.
[0013] In the present invention, the surface deposition-crosslinking method is first used to precipitate chitosan (CS) from the first chitosan solution and deposit it on the surface of carbon nanotubes (CNT), and then the CS deposited on the surface of CNT is crosslinked by a crosslinking agent to prepare chitosan-coated carbon nanotubes (CS@CNT). Secondly, CS@CNT is reacted with a citric acid solution, and citric acid molecules are introduced into the CS@CNT structure by utilizing the interaction between the amino group and the carboxyl group in the CS@CNT structure to prepare chitosan-modified carbon nanotubes CCS@CNT, which is actually a chitosan-coated carbon nanotube citric acid hybrid material. CCS@CNT is then mixed with the raw materials of MOFs for in-situ reaction, and MOFs / modified carbon nanotubes are prepared by utilizing the strong metal ion chelating ability of citric acid molecules. Finally, the prepared MOFs / modified carbon nanotubes were doped with chitosan at different mass fractions to prepare a composite proton exchange membrane based on MOFs / modified carbon nanotubes. The obtained composite proton exchange membrane is based on chitosan and doped with MOFs / modified carbon nanotubes. The mechanical properties and proton conduction properties of the composite proton exchange membrane are relatively excellent.
[0014] Preferably, in step (1), the first chitosan solution is obtained by mixing chitosan and acetic acid aqueous solution in a ratio of (1.0-1.5) g: (40-100) mL; the volume concentration of the acetic acid aqueous solution is 0.5-1.5%.
[0015] Preferably, in step (1), the mass ratio of chitosan to carbon nanotubes in the first chitosan solution is (1.0-1.5): (0.3-0.5).
[0016] Preferably, in step (1), the pH value of the first dispersion is adjusted to alkaline, specifically, the pH value of the first dispersion is adjusted to 9-10 using ammonia water.
[0017] Preferably, in step (1), the cross-linking agent comprises glutaraldehyde; and the ratio of chitosan to the cross-linking agent in the first chitosan solution is (1.0-1.5) g: (1.0-1.5) mL.
[0018] Preferably, in step (1), the cross-linking reaction is carried out at room temperature for 0.8 to 1.2 hours.
[0019] Preferably, in step (1), after the cross-linking reaction is completed, chitosan-coated carbon nanotubes CS@CNT are obtained by centrifugal separation and washing with acetic acid solution.
[0020] Preferably, in step (2), the ratio between CS@CNT and citric acid solution is (0.8-1.2) g:100 mL; and the concentration of citric acid solution is 2-4 mol / L.
[0021] Preferably, in step (2), the reaction is first carried out at 75-85 o C for 10 to 14 hours. After the reaction solution is cooled to room temperature, alkaline solution is added dropwise to adjust the pH value to 4.5 to 5.5, and the solution is allowed to stand for 0.8 to 1.2 hours.
[0022] Preferably, in step (2), after the reaction is completed, the chitosan-modified carbon nanotubes CCS@CNT are obtained by centrifugation, washing with deionized water and freeze-drying.
[0023] Preferably, in step (3), the organic solvent includes N,N-dimethylformamide (DMF); and the ratio of CCS@CNT to the organic solvent is (1.0-1.5) g: (40-80) mL.
[0024] Preferably, in step (3), the raw materials of MOFs include zinc salt and 2-aminoterephthalic acid; the mass ratio of CCS@CNT, zinc salt and 2-aminoterephthalic acid is (1.0-1.5): (0.8-1.0): (1.0-1.5); the zinc salt includes Zn(Ac)2﹒2H2O (zinc acetate dihydrate) or zinc nitrate hexahydrate. In the present invention, CCS@CNT is reacted with 2-aminoterephthalic acid and zinc salt in situ, and MOFs / modified carbon nanotubes are prepared by utilizing the strong metal ion chelating ability of citric acid molecules; the MOFs are based on Zn 2+ The complex (ZnBDC) is the central ion and terephthalic acid is the organic ligand, so the obtained MOFs / modified carbon nanotubes are ZnBDC / CCS@CNT hybrid materials.
[0025] Further preferably, in step (3), the raw material of MOFs is added to the second dispersion to obtain MOFs / modified carbon nanotubes through in-situ reaction, which specifically includes: adding zinc salt to the second dispersion, stirring at room temperature for 20 to 40 minutes, then adding 2-aminoterephthalic acid to fully dissolve, reacting at 110 to 130° C. for 4 to 6 hours, cooling, centrifuging, washing and drying to obtain MOFs / modified carbon nanotubes.
[0026] Preferably, in step (4), the second chitosan solution is obtained by mixing chitosan and acetic acid aqueous solution in a ratio of (0.8-1.0) g: (30-40) mL; the volume concentration of the acetic acid aqueous solution is 0.5-1.5%.
[0027] Preferably, in step (4), the mass ratio of chitosan to MOFs / modified carbon nanotubes in the second chitosan solution is 100:(1-5).
[0028] Preferably, in step (4), the casting liquid is subjected to film casting to form a film, specifically comprising: casting the casting liquid into a clean glass plate casting tank, drying at 35-45° C. for 11-13 hours, then washing with deionized water, soaking in 2 mol / L sulfuric acid for 20-28 hours, washing to neutrality and drying to obtain a composite proton exchange membrane based on MOFs / modified carbon nanotubes.
[0029] In a second aspect, the present invention provides a composite proton exchange membrane based on MOFs / modified carbon nanotubes prepared by the above preparation method.
[0030] The main mechanism of action and advantages of the present invention: (1) The present invention adopts a simple surface deposition method, firstly, using chitosan to coat the surface of CNT, so as to strengthen the interface interaction between CNT and chitosan matrix, and improve the dispersibility of CNT in chitosan matrix. On this basis, taking advantage of the fact that the surface of chitosan-coated carbon nanotubes CS@CNT contains abundant amino groups (-NH2) and hydroxyl groups (-OH), citric acid molecules are connected through chemical reaction, and the strong metal ion chelating and coordination ability of citric acid molecules is utilized to enhance the effective interaction between MOFs and CNT, and realize the controllable preparation of conductive MOFs on the surface of CNT, and then prepare a new proton exchange membrane by compounding with chitosan matrix; and the performance of the obtained composite proton exchange membrane is effectively regulated by the addition amount of MOFs / modified carbon nanotubes.
[0031] (2) The present invention combines conductive MOFs materials with CNTs, and regulates the in-situ preparation process of MOFs on the surface of CCS@CNTs to achieve uniform dispersion of MOFs on the surface of CCS@CNTs, and prepares a composite material system with synergistic interactions, showing unique performance advantages: First, by utilizing the unique morphological characteristics and surface functional group structure of CNTs, the dispersibility of MOFs materials is effectively improved by combining MOFs with CNTs in situ. In addition, by combining the CNT morphology and the characteristics of MOFs porous materials, a proton transport channel with a long-range continuous channel can be formed, which is conducive to maximizing the performance advantages of MOFs in proton conduction. Moreover, the rich directional modification characteristics of MOFs in the structure provide the possibility of preparing materials with different functional properties.
[0032] The present invention is further described in detail below through specific examples, wherein the chitosan used has a molecular weight of 500,000 and a deacetylation degree of 92% (purchased from Zhejiang Jinke Biochemical Co., Ltd.); the acetic acid aqueous solution used is prepared by mixing laboratory-made pure water with analytically pure acetic acid, and the acetic acid is analytically pure (purchased from Sinopharm Group).
[0033] Example 1 A method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes, the steps are as follows: (1) Dissolve 1.0 g chitosan (CS) in 40 mL acetic acid aqueous solution (1 vol.%), then add 0.3 g CNT to the solution, and stir under ultrasound until it is evenly dispersed. Subsequently, add dilute ammonia water to the system to adjust the pH to 9.5, so that CS precipitates from the solution and deposits on the surface of CNT. Next, add 1.0 mL glutaraldehyde to the system at room temperature to cross-link the CS deposited on the CNT surface, and continue the reaction for 1 hour. Finally, collect the sample by centrifugation, and wash the uncross-linked CS in the sample with dilute acetic acid solution (1 vol.%) to obtain CS@CNT.
[0034] (2) Add 1.0 g of CS@CNT prepared in step (1) to 100 mL of 3 mol / L citric acid solution. o C for 12 h, and then the reaction solution was cooled to room temperature, and 4 mol / L sodium hydroxide solution was slowly added to adjust the pH value to 5. The solution was then allowed to stand for 1 h, and then the solution was centrifuged, and the solid was washed with deionized water to a pH value of 7, and finally freeze-dried for 12 h to obtain CCS@CNT.
[0035] (3) Disperse 1.0 g of CCS@CNT prepared in step (2) in 60 mL of DMF and disperse evenly by ultrasonic treatment. Then add 0.8 g of Zn(Ac)2﹒2H2O and stir at room temperature for 30 min. Then add 1.0 g of 2-aminoterephthalic acid and dissolve it fully by ultrasonic treatment. Then transfer the solution to a reactor and heat at 120 o C was reacted for 5 h, then naturally cooled to room temperature, separated by centrifugation, and the solid was washed twice with ethanol and deionized water respectively, and finally dried to obtain solid powder MOFs / modified carbon nanotubes (ZnBDC / CCS@CNT).
[0036] (4) 1.0 g of CS was dissolved in 40 mL of acetic acid solution (1 vol.%). After it was fully dissolved, 0.01 g of ZnBDC / CCS@CNT was added and then stirred by ultrasonic treatment to form a uniformly dispersed solution. Subsequently, the mixed solution was cast into a clean glass plate casting tank and placed in a 40 oAfter removal, soak in a large amount of deionized water until neutral, and then soak in 100mL 2M sulfuric acid solution for 24h to crosslink. Finally, wash thoroughly with deionized water until neutral, and then rinse in 40 o C drying to obtain a composite proton exchange membrane, denoted as ZnBDC / CCS@CNT / CS / 1%.
[0037] Example 2 The preparation method of this embodiment is the same as that of embodiment 1, except that 0.03 g of ZnBDC / CCS@CNT is added in step (4) of this embodiment to obtain a composite proton exchange membrane ZnBDC / CCS@CNT / CS / 3%.
[0038] Example 3 The preparation method of this embodiment is the same as that of embodiment 1, except that 0.05 g of ZnBDC / CCS@CNT is added in step (4) of this embodiment to obtain a composite proton exchange membrane ZnBDC / CCS@CNT / CS / 5%.
[0039] Comparative Example 1 A method for preparing a proton exchange membrane, comprising the following steps: 1.0 g CS was dissolved in 40 mL 1% acetic acid solution. After it was fully dissolved, it was stirred at room temperature to form a uniformly dispersed solution. Then, the mixed solution was cast into a clean glass plate casting tank and placed in 40 o After removal, soak in a large amount of deionized water until neutral, and then soak in 100 mL of 2M sulfuric acid for 24 hours to crosslink. Finally, wash thoroughly with deionized water until neutral, and then 40 o C drying to obtain pure chitosan film.
[0040] Performance Testing The test conditions of the membrane performance prepared in each embodiment and comparative example are described as follows: (1) Proton conductivity: The resistance of the membrane was tested using the AC impedance method on a frequency response analyzer with a frequency sweep range of 1-10 7 Hz, the AC signal amplitude is 100mV. The cut membrane (1.5cm×2.5cm) was tested by two-electrode AC impedance method. Before the test, the membrane sample was placed in deionized water at room temperature to reach saturation. The proton conductivity σ (S / cm) of the membrane was calculated by the following formula:
[0041] Wherein, L and A are the distance between the two electrodes and the effective cross-sectional area of the membrane to be tested between the two electrodes, respectively, and R is the resistance of the membrane, which is calculated from the data obtained from the AC impedance test.
[0042] (2) Tensile strength and elongation at break: The film was cut into rectangular strips with a length of 40 mm and a width of 20 mm. The test was performed on an electronic tensile testing machine at a tensile speed of 2 mm / min. The test was carried out at room temperature.
[0043] The ZnBDC / CCS@CNT / CS proton exchange membranes prepared in Examples 1 to 3 and the pure chitosan membrane prepared in Comparative Example 1 were subjected to tensile property tests, and the results are shown in Table 1.
[0044] Table 1 Tensile performance test data
[0045] As can be seen from Table 1, the composite proton exchange membrane prepared in the present invention shows good mechanical properties. Compared with the pure CS membrane, the mechanical properties, especially the tensile strength, are greatly improved, wherein the tensile strength is above 32 MPa, and the highest tensile strength reaches 45 MPa, which is greatly improved compared with the pure chitosan membrane of Comparative Example 1; the elongation at break of Examples 1 to 3 has no obvious change relative to Comparative Example 1, indicating that the added ZnBDC / CCS@CNT has no effect on the elongation at break of the chitosan matrix.
[0046] The proton conductivity of the ZnBDC / CCS@CNT / CS proton exchange membranes prepared in Examples 1 to 3 and the pure chitosan membrane prepared in Comparative Example 1 was tested, and the results are shown in Table 2.
[0047] Table 2 Proton conductivity
[0048] The proton conduction test in Table 2 shows that the composite proton exchange membrane ZnBDC / CCS@CNT / CS / 3% prepared in Example 2 exhibits good proton conduction performance, wherein the highest proton conductivity at 80°C is 28.6 mS / cm, which is also significantly improved compared with the pure chitosan membrane.
[0049] The present invention provides a stable composite proton exchange membrane based on MOFs / modified carbon nanotubes and a preparation method thereof, the method comprising the following steps: 1) preparing chitosan-coated carbon nanotubes; 2) introducing citric acid molecules into the CS@CNT structure by reacting CS@CNT with a citric acid solution to prepare chitosan-modified carbon nanotubes (CCS@CNT); 3) reacting chitosan-modified carbon nanotubes (CCS@CNT) with 2-aminoterephthalic acid and zinc salt in situ to prepare MOFs / modified carbon nanotubes; 4) doping the prepared MOFs / modified carbon nanotubes with chitosan at different mass fractions to prepare composite proton exchange membranes with different MOFs / modified carbon nanotube contents. The present invention utilizes the structural and performance characteristics of CNTs to construct a stable MOFs / modified carbon nanotube system, and chitosan coating can effectively strengthen the interface interaction between CNT and chitosan matrix, and improve the dispersibility of CNT in the chitosan matrix. The introduction of citric acid molecules can effectively enhance the effective interaction between MOFs and CNTs, realize the controllable preparation of conductive MOFs on the CNT surface, and effectively improve the mechanical properties and proton conductivity of chitosan proton exchange membranes.
[0050] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes, characterized in that: The following steps are involved: Add carbon nanotubes to the first chitosan solution and disperse them evenly, adjust the pH value to alkaline, add a cross-linking agent to carry out a cross-linking reaction, and obtain CS@CNT; Adding the CS@CNT into a citric acid solution to react, thereby obtaining CCS@CNT; The CCS@CNT is added into an organic solvent, and then into a raw material of MOFs, and MOFs / modified carbon nanotubes are obtained through an in-situ reaction; The MOFs / modified carbon nanotubes are added to the second chitosan solution to obtain a casting solution, and a composite proton exchange membrane based on MOFs / modified carbon nanotubes is obtained by film casting.
2. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The steps of adding carbon nanotubes to the first chitosan solution to disperse them uniformly and adjusting the pH value to alkaline, and adding a crosslinking agent to carry out a crosslinking reaction to obtain CS@CNT specifically include: Adding carbon nanotubes to the first chitosan solution and dispersing them evenly to obtain a first dispersion; adjusting the pH value of the first dispersion to 9-10 with ammonia water, and then adding a crosslinking agent to perform a crosslinking reaction to obtain CS@CNT; The first chitosan solution is obtained by mixing chitosan and acetic acid aqueous solution in a ratio of (1.0-1.5) g: (40-100) mL; the volume concentration of the acetic acid aqueous solution is 0.5-1.5%; The mass ratio of chitosan in the first chitosan solution to the carbon nanotubes is (1.0-1.5): (0.3-0.5); The cross-linking agent includes glutaraldehyde; the ratio of chitosan in the first chitosan solution to the cross-linking agent is (1.0-1.5) g: (1.0-1.5) mL; The cross-linking reaction is carried out at room temperature for 0.8 to 1.2 hours.
3. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The ratio between the CS@CNT and the citric acid solution is (0.8-1.2) g:100 mL; the concentration of the citric acid solution is 2-4 mol / L.
4. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The CS@CNT is added to a citric acid solution for reaction, specifically comprising: firstly o C for 10 to 14 hours. After the reaction solution is cooled to room temperature, alkaline solution is added dropwise to adjust the pH value to 4.5 to 5.5, and the solution is allowed to stand for 0.8 to 1.2 hours.
5. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The organic solvent includes N,N-dimethylformamide (DMF); the ratio of CCS@CNT to the organic solvent is (1.0-1.5) g: (40-80) mL.
6. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The raw materials of the MOFs include zinc salt and 2-aminoterephthalic acid; The mass ratio of the CCS@CNT, the zinc salt and the 2-aminoterephthalic acid is (1.0-1.5): (0.8-1.0): (1.0-1.5); The zinc salt includes zinc acetate or zinc nitrate.
7. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 6, characterized in that: The step of adding the CCS@CNT into an organic solvent, and then adding the raw material of MOFs, and obtaining MOFs / modified carbon nanotubes through in-situ reaction specifically includes: The CCS@CNT is added to an organic solvent and dispersed evenly to obtain a second dispersion; zinc salt is added to the second dispersion, stirred at room temperature for 20 to 40 minutes, 2-aminoterephthalic acid is added to fully dissolve, reacted at 110 to 130° C. for 4 to 6 hours, cooled, centrifuged, washed and dried to obtain MOFs / modified carbon nanotubes.
8. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The second chitosan solution is obtained by mixing chitosan and acetic acid aqueous solution in a ratio of (0.8-1.0) g: (30-40) mL; The mass ratio of chitosan in the second chitosan solution to the MOFs / modified carbon nanotubes is 100:(1-5).
9. The method for preparing a composite proton exchange membrane based on MOFs / modified carbon nanotubes according to claim 1, characterized in that: The casting film forming specifically includes: casting the casting liquid into a clean glass plate casting tank, drying at 35-45°C for 11-13 hours, then washing with deionized water, soaking in 2mol / L sulfuric acid for 20-28 hours, washing to neutrality and drying to obtain a composite proton exchange membrane based on MOFs / modified carbon nanotubes.
10. A composite proton exchange membrane based on MOFs / modified carbon nanotubes prepared according to the preparation method according to any one of claims 1 to 9.
